Trust and Communication Foundations of Interconnectivity - Kunnel, Anil Jacob (Peter Lang International Academic Publishers, 2021)
In today's global and digitalized world, the investigation of relational trust as part of social connections has remained a popular and interdisciplinary academic topic. This book explores the idea of trust as a basic type of information processing that might be as old as human existence but has gained new attention with the emergence of online communication channels. The result is a strategic reconsideration of the brain's role in the formation of social relationships and a new look at how information might shape our confidence in others.